'Nature Knows No Boundaries': The Role of Nature Conservation in Peacebuilding. (May 2017) - Roulin, Alexandre; Abu Rashid, Mansour; Spiegel, Baruch; Charter, Motti; Dreiss, Amélie N.; Leshem, Yossi
Abstract : Humanity is facing a biodiversity crisis. To solve environmental problems, we bring people from Israel, Jordan, and the Palestinian Authority to the same table. Conservation efforts are beneficial for all communities and facilitate constructive dialog across divides in conflict zones. This pleads for the integration of nature conservation into peacebuilding interventions.